Isotherm Study and Interaction Consideration of Samarium(III) with New Modified Siliceous Support - Moniri, Elham; Ahmad Panahi, Homayon; Mahdavi Jalal, Mohammadreza; Gaforiyan, Hossein (Asian Journal of Chemistry, 2012)
A new sorbent was prepared by surface grafting of polymer containing a functional monomer, poly[iminodiacetic acid-allylglycidyl-co-methylacrylamide] (poly(IDA/AGE-DMAA) onto a modified silica. The silica surface was modified by silylation with 3-mercaptopropyltrimethoxysilane followed by graft polymerization. The resulting sorbent has been characterized by FT-IR. The optimum pH value for sorption of the metal ion was 5. The equilibrium adsorption data of Sm(III) on modified sorbent were analyzed by Langmuir, Freundlich, Temkin and Redlich-Peterson models. Based on equilibrium adsorption data the Langmuir, Freundlich and Temkin constants were determined 55.06, 0.398 and 0.2, respectively at pH 5 and 20 ºC.